2014
DOI: 10.1182/blood-2013-10-525634
|View full text |Cite
|
Sign up to set email alerts
|

A Caenorhabditis elegans–based assay recognizes immunoglobulin light chains causing heart amyloidosis

Abstract: Key Points• C elegans specifically recognizes cardiotoxic LCs as toxicants.• This is an innovative model for studying the heart-specific toxicity of amyloidogenic LCs and developing new therapeutic strategies.Poor prognosis and limited therapeutic options characterize immunoglobulin light-chain (AL) amyloidosis with major heart involvement. Reliable experimental models are needed to study light-chain (LC)/heart interactions and to explore strategies for prevention of cardiac damage. We have exploited the nemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
163
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(183 citation statements)
references
References 49 publications
15
163
1
4
Order By: Relevance
“…25 The results obtained indicated that, contrary to what observed with the Ab proteins, the pharyngeal dysfunction caused by cardiotoxic LC was not related to a peculiar protein folding, oligomerization propensity nor to different size; instead, it was due to their peculiar ability to continuously generate reactive oxygen species (ROS). 25 This renders these proteins recognizable as stressors from C. elegans, which reacts by ceasing the feeding. Once ingested, LC produce cellular oxidative damage and increase mitochondrial ROS, which contribute to sustaining the permanent pharyngeal dysfunction and shorting their lifespans 25 ( Fig.…”
contrasting
confidence: 49%
See 3 more Smart Citations
“…25 The results obtained indicated that, contrary to what observed with the Ab proteins, the pharyngeal dysfunction caused by cardiotoxic LC was not related to a peculiar protein folding, oligomerization propensity nor to different size; instead, it was due to their peculiar ability to continuously generate reactive oxygen species (ROS). 25 This renders these proteins recognizable as stressors from C. elegans, which reacts by ceasing the feeding. Once ingested, LC produce cellular oxidative damage and increase mitochondrial ROS, which contribute to sustaining the permanent pharyngeal dysfunction and shorting their lifespans 25 ( Fig.…”
contrasting
confidence: 49%
“…Interestingly, we observed that only amyloidogenic LC that are cardiotoxic in AL patients caused a specific impairment of the pharyngeal pumping in C. elegans. 25 This effect is dose-dependent and is maximal at concentrations comparable to those commonly found in blood of patients with AL amyloidosis. 25,19,20 We also observed that the pharynx functionality is selectively impaired and, since the C. elegans external cuticle is quite impermeable, it cannot be dismissed that the restriction of the effect only to this organ is due to the high local concentration of the toxic LC.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…3 Clinical and experimental evidence indicate that cardiac damage in AL amyloidosis is mainly determined by a direct toxicity exerted by the circulating amyloidogenic free light chain (FLC). [4][5][6][7][8] Thus, therapy of AL amyloidosis is aimed at obtaining a rapid and profound FLC reduction by targeting the amyloidogenic plasma cell clone with chemotherapy, while attentively supporting involved organ function. Treatment approaches are derived from multiple myeloma and are adapted to the fragile amyloid patients, and novel agents are finding their place in the therapeutic armamentarium for AL amyloidosis.…”
Section: Introductionmentioning
confidence: 99%